CREATION AS A CONDITION FOR PERSONAL EXPRESSION AND INDIVIDUATION - Lescinskaite, Irma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the basic concepts and theories of creation and creativity. Creativity is not applied to action, but is rather a psychological quality of a person that is manifested through certain abilities. The question is whether creativity is considered to be determined by spontaneous, irrational factors or can be promoted and is a stimulating phenomenon. The concept of Creativity, its features, as well as traits of a creative personality are distinguished. The following articles also discusses principles, prerequisites for creative motivation – when people become most creative. Creativity is universally considered to be a distinctive feature of a matured, multifaceted and self-realizing, and thus individualized personality. Creative abilities, as a transforming force, enhance a person’s sense of value, accelerate the individual’s self-fulfilment and maturation of personality.